Bismuth-based semiconductors applied in photocatalytic reduction processes: fundamentals, advances and future perspectives. Issue 29 (21st March 2023) - Shi, Meng; Yang, Huiying; Zhao, Zehui; Ren, Guangmin; Meng, Xiangchao
Abstract : Bismuth-based semiconductors applied in photocatalytic reduction are summarized and discussed. Future research directions are proposed. Abstract : Bismuth-based semiconductors (BBSs) with their typical layered structures and unique electronic properties are considered an attractive visible light-responsive photocatalysts. Recently, BBS exhibited promising properties and was rapidly developed in photoreduction reactions. In this review, we firstly focus on the photoreduction reactions of BBS with a description of the basic principles. Specifically, the restrictive factors of the photoreduction reactions and the design directions of the catalysts are addressed. BBS photocatalysts, such as bismuth oxide, bismuth halide oxide and bismuth-based oxygenates, are presented in terms of the catalyst material design, crystal structure and other features. Furthermore, the primary applications of BBS in photoreduction reactions are described, including CO2 reduction, N2 reduction, H2 evolution, and nitrate reduction. Additionally, the advances and shortages of BBS applied in these processes are summarized and comprehensively discussed. Future works for BBS applied in photoreduction processes are also proposed.